Rethinking Fiscal Self-Reliance: Sectoral Dynamics of Industrialization and Agriculture in Indonesia’s Local Economies - iis surgawati; irman firmansyah (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2026)
Fiscal self-reliance of local governments has become a crucial issue in Indonesia’s fiscal decentralization era, as it reflects a region’s capacity to finance development without excessive dependence on central government transfers. This study aims to analyze the effects of economic growth rate, Gross Regional Domestic Product (GRDP) in the industrial sector, GRDP in the agricultural sector, and regional asset values on the level of fiscal self-reliance across 100 regencies/municipalities in six major island regions of Indonesia during the 2019–2023 period. Utilizing a fixed-effects panel data regression model and comprehensive statistical diagnostics, the study controls for interregional heterogeneity to obtain robust estimates. The results show that industrial GRDP and regional asset values have a positive and significant impact on fiscal self-reliance, indicating that industrialization and optimal public asset management are key drivers in strengthening locally generated revenue. Conversely, agricultural GRDP and economic growth rate do not exhibit a significant effect, reflecting the limited capacity of these sectors in supporting local fiscal strength primarily due to the dominance of informal activities and weak fiscal integration. These findings affirm that fiscal self-reliance cannot be built solely through economic growth; rather, it requires structural transformation focused on high value-added sectors and institutional strengthening in regional asset management. Policy implications include the need to reformulate sectoral fiscal strategies and enhance asset governance as concrete steps toward sustainable and equitable fiscal decentralization.